Оптико-электронные средства обнаружения - Сергиенко, С. И.; Заворотна, М. Г. (ХНУРЕ, 2019)
Today, many problems of detection, observation, guidance and tracking are solved with the direct use of optical and optical-electronic means, whose role is increasing from year to year. Of particular relevance is the problem of observation in low light conditions acquired during the Second World War. Its practical implementation provided an opportunity to act at dusk and at night without using visible light sources. With the help of them it is possible to conduct ground, sea and air reconnaissance of the enemy and the terrain in virtually any terrain conditions, weather and time of day. Exploration can be conducted from open and hidden observation posts to a depth of several kilometers. But they have their pros and cons.
Keywords: опто-електронні засоби; задача виявлення; задача спостереження; задача наведення